2019
DOI: 10.1002/acm2.12512
|View full text |Cite
|
Sign up to set email alerts
|

90Y SPECT/CT quantitative study and comparison of uptake with pretreatment 99 mTc‐MAA SPECT/CT in radiomicrosphere therapy

Abstract: IntroductionYttrium‐90 (90Y) microsphere post‐treatment imaging reflects the true distribution characteristics of microspheres in the tumor and liver compartments. However, due to its decay spectra profile lacking a pronounced photopeak, the bremsstrahlung imaging for 90Y has inherent limitations. The absorbed dose calculations for 90Y microspheres radiomicrosphere therapy (RMT) sustain a limitation due to the poor quality of 90Y imaging. The aim of this study was to develop quantitative methods to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Prospective treatment planning with pre-therapy 99m Tc-MAA SPECT has demonstrated a good correlation between tumour dose and response [35] , [36] , [37] . However, studies have shown contrasting findings when investigating the predictive power of the pre-therapy 99m Tc-MAA distribution [16] , [17] , [19] , [20] , [38] , [39] , [40] . To allow direct quantitative comparison between predicted and delivered 90 Y absorbed dose, a novel RCM method was developed to address the differences in partial volume effects between 99m Tc-MAA SPECT and 90 Y bremsstrahlung SPECT images by converting the spatial resolution of the pre-therapy scan data to that of the post-therapy scan data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective treatment planning with pre-therapy 99m Tc-MAA SPECT has demonstrated a good correlation between tumour dose and response [35] , [36] , [37] . However, studies have shown contrasting findings when investigating the predictive power of the pre-therapy 99m Tc-MAA distribution [16] , [17] , [19] , [20] , [38] , [39] , [40] . To allow direct quantitative comparison between predicted and delivered 90 Y absorbed dose, a novel RCM method was developed to address the differences in partial volume effects between 99m Tc-MAA SPECT and 90 Y bremsstrahlung SPECT images by converting the spatial resolution of the pre-therapy scan data to that of the post-therapy scan data.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a number of reasons why this assumption may be flawed which include differences in the size and number of particles administered [12] , the catheter position [13] , [14] , [15] , administration flow rates [13] , [14] , [15] and regional blood flow differences between administrations [16] . Previous studies have compared the pre- and post-therapy imaging [14] , [17] , [18] , [19] , [20] , [21] , with the majority of these studies taking no account of the differences in the partial volume effect of the images [14] , [17] , [18] , [19] . However, Gnesin et al [20] applied recovery coefficients to predicted and delivered absorbed doses to tumours derived from 99m Tc-MAA SPECT and 90 Y PET images respectively, while a recent study by Mikell et al [21] convolved 90 Y PET images with a Gaussian function to match the spatial resolution of 99m Tc-MAA SPECT images.…”
Section: Introductionmentioning
confidence: 99%